2017
DOI: 10.1097/crd.0000000000000114
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in Ischemic Heart Disease

Abstract: Despite rapid advances in cardiovascular research and therapeutic strategies, ischemic heart disease (IHD) remains the leading cause of mortality worldwide. MicroRNAs (miRNAs) are small, noncoding RNAs which post transcriptionally regulate gene expression. In the past few years, miRNAs have emerged as key tools for the understanding of the pathophysiology of IHD, with potential uses as new biomarkers and therapeutic targets. Several studies report a regulatory role of miRNAs, with regard to fundamental compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 99 publications
0
18
0
6
Order By: Relevance
“…Evidence suggesting the epigenetic control of angiogenesis has been accumulating, particularly through noncoding microRNAs (miRNAs), which induce messenger RNA degradation or block translation (21). Since they target multiple genes rapidly, miRNAs are well positioned to regulate complex processes such as angiogenesis (30,67,92,177). ECs express several miRNAs that are induced by hypoxia or VEGF during adaptive remodeling or acute ischemia (111,135).…”
Section: Micrornasmentioning
confidence: 99%
“…Evidence suggesting the epigenetic control of angiogenesis has been accumulating, particularly through noncoding microRNAs (miRNAs), which induce messenger RNA degradation or block translation (21). Since they target multiple genes rapidly, miRNAs are well positioned to regulate complex processes such as angiogenesis (30,67,92,177). ECs express several miRNAs that are induced by hypoxia or VEGF during adaptive remodeling or acute ischemia (111,135).…”
Section: Micrornasmentioning
confidence: 99%
“…MicroRNAs (miRNAs), a type of non-coding RNAs, are vital post-transcriptional modulators, which participate in a myriad of physiological functions and pathological conditions (such as endothelial homeostasis, glucolipid metabolism as well as microangiopathy), and part of them have been found to regulate several hemostatic factors, tissuefactors or anti-angiogenic factors to play essential roles in coagulation that is a critical step for thrombosis of MACCE [9][10][11][12]. Considering the crucial status of coagulation on affecting MACCE occurrence as we mentioned above, and miRNAs have regulatory effects in coagulation process, we hypothesized that the blood coagulation related miRNAs might be associated with MACCE risk or related prognosis, which might serve as markers for MACCE in CAPD patients, while related evidence is seldomly reported [12,13]. In this study, 13 blood coagulation related miRNAs were selected referring to a recent review analysis focusing on hemostasis and coagulation pathways related miRNAs, and we aimed to investigate the correlation of these coagulation related miRNAs expressions with MACCE risk in patients undergoing long-term CAPD [14].…”
Section: Introductionmentioning
confidence: 95%
“…It is commonly known that levels of certain circulating miRNAs might be predictive for long-term diabetes complications [22]. MiRNAs may be a usefull biomarker because of its stability in bio uids even after prolonged time since collection and several freezing-thaw cycles [23]. Moreover, those small particles can be easily collected and measured with speci c, sensitive assays [22].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that miRNAs play an important role in the development of heart diseases. It has been proven that miRNAs (miR-33, miR-144, miR-30c, miR-378, miR-96, miR-185) are involved in maintaining of lipoprotein homeostasis by regulation of cholesterol transport and its uptake [23]. MiRNAs such as miR-92a, miR-503, miR-126 can also control and regulate angiogenesis, crucial for the repair of myocardial cells after ischemic injury [24,25].…”
Section: Introductionmentioning
confidence: 99%